Sheep in Wolves’ Clothing: How Composition’s Social Construction Reinstates Expressivist Solipsism (And Even Current-Traditional Conservatism) - Keith Rhodes; Monica M Robinson (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Reframing the theory of social construction from Romantic/ Classic perspectives yields surprising insights about writing studies.